Universal Dynamic Liquid Interface for Healing Perovskite Solar Cells. Issue 26 (24th May 2022) - Guo, Qiyao; Duan, Jialong; Zhang, Junshuai; Zhang, Qiaoyu; Duan, Yanyan; Yang, Xiya; He, Benlin; Zhao, Yuanyuan; Tang, Qunwei
Abstract: Healing charge‐selective contact interfaces in perovskite solar cells (PSCs) highly determines the power conversion efficiency (PCE) and stability. However, the state‐of‐the‐art strategies are often static by one‐off formation of a functional interlayer, which delivers fixed interfacial properties during the subsequent operation. As a result, defects formed in‐service will gradually deteriorate the photovoltaic performances. Herein, a dynamic healing interface (DHI) is presented by incorporating a low‐melting‐point small molecule onto perovskite film surface for highly efficient and stable PSCs. Arising from the reduced non‐radiative recombination, the DHI boosts the PCE to 12.05% for an all‐inorganic CsPbIBr2 solar cell and 14.14% for a CsPbI2 Br cell, as well as 23.37% for an FA0.92 MA0.08 PbI3 (FA = formamidinium, MA = methylammonium) cell. The solid‐to‐liquid phase conversion of DHI at elevated temperature causes a longitudinal infiltration into the bulk perovskite film to maximize the charge extraction, passivate defects at grain boundaries, and suppress ion migration. Furthermore, the stability is remarkably enhanced under air, heat, and persistent light‐irradiation conditions, paving a universal strategy for advanced perovskite‐based optoelectronics. Abstract : A universal method of creating a dynamic healing interface (DHI) is launched by reinforcing the defective surface and grain boundaries of perovskite film with nonvolatile 2‐bromonaphthalene (BN) with a low melting point of 53–58 °C. Different from static interfaces, the fluid characteristic originating from the easy solid‐to‐liquid phase conversion of the DHI not only reinforces management of defect passivation and energetics modification, but also enables effective defect real‐time self‐healing. High efficiencies are thus achieved for popular PSCs up to 12.05% (CsPbIBr2 ), 14.14% (CsPbI2 Br), and 23.37% (FA0.92 MA0.08 PbI3 ).